Digital Ethnography of Nongnong Mbaham: Oral Literature Revitalization for Cultural Identity and Contextual Learning Innovation in Papuan Education - Adolina Velomena Samosir Lefaan; Rommy Denny Boy Rambet; Susi Darihastining; Siti Maisaroh (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study investigates Nongnong Mbaham as a living oral tradition, examines its transformation within digital environments, and explores its potential as a contextual learning innovation in Papuan educational settings. Methodology: A qualitative digital ethnographic approach was employed, involving participant observation, in-depth interviews, performative analysis, and digital-trace analysis across offline and online cultural spaces. Main Findings: This study demonstrates that indigenous oral literature can function as a culturally grounded learning resource that supports identity formation, digital literacy, and contextual pedagogy. Novelty/Originality of this study: This research advances oral-literature studies by integrating digital ethnography with contextual learning innovation, moving beyond documentation toward a sustainable educational revitalization model.